STtTDIElS ON THE MORTALITY IN SPAWN AND FRY OF INDIAN MAJOR CARPS DURING TRANSPORT Part IV. Types of Containers Used for Transporting Spawn and Fry under Oxygen Pressure - Saha, K C; Sen, D P (Indian Journal of Fisheries, 2016)
For transporting the fry of Indian major carps, three types of containers,viz., glass carboy, specially designed aluminium and galvanizediron sheet containers and latex-rubber and plastic bags, have been described.Although from the point of view of efficiency the specially designed aluminiumcontainer has been found most suitable, considering the relative costsof different types of containers tried, latex-rubber bag may be recommendedfor commercial use.